Development and assessment of propranolol sustained release dosage forms separately and in combination with hydrochlorothiazide - Chetty, Prakash (Rhodes University, Faculty of Pharmacy, Pharmacy, 2006)
Hypertension is a chronic illness that is often undiagnosed and untreated leading to high mortality rates in South Africa. The use of diuretics such as hydrochlorothiazide and beta blockers such as propranolol has been advocated as first line therapy for the treatment of hypertension. The study and use of controlled release dosage forms for the treatment of various disease states has gained wide interest over the past two decades. The use of controlled release systems offers improved therapeutic efficiency over conventional immediate release dosage forms, the use of which at times have often led to poor patient adherence and decreased therapeutic efficiencies. The current research objective was to develop a sustained release multi-source product for propranolol such that once daily dosing would be achieved. In addition, the sustained release product was developed using InderalÂ® LA 80mg capsules as a reference product. In addition the development of a suitable immediate release hydrochlorothiazide tablet was undertaken to produce a combination dosage form. The use of two different technologies, namely direct compression and wet granulation were employed to develop the sustained release dosage form. The release of propranolol from these dosage forms was assessed using USP apparatus 1 with quantitation of the relevant dissolution samples using a validated high performance liquid chromatographic method. The release profiles from the prototype and subsequent products were subjected to model independent and model dependent analyses in order to compare them to the innovator product and to elucidate the mechanisms of drug release respectively. Dissolution test results reveal that dosage forms prepared from wet granulation showed better rate retardation and more appropriate release profiles than those prepared by direct compression techniques. The subsequent model independent and model dependent analysis show that a dosage form that is comparable to the innovator product has been developed, with drug release occurring by a diffusion type mechanism.
Keywords: Uncatalogued